Assessment of schedulable potential for user-side resources participating in demand response based on improved G1 method using SRC - Wu, Hairu; Yang, Maotao; Wu, Rong; Fan, Qingchuan; Chen, Xiangyuan; Xiao, Jianhong (Frontiers in Energy Research, 2023)
The aggregation of user-side resources to participate in demand response (DR) can improve the stability and economy of power supply. An improved G1 method using Spearman rank correlation (SRC) is proposed to evaluate the schedulable potential for user-side resources. Firstly, the DR potential evaluation indicator was established based on the characteristics of user-side resources. Secondly, the resource potential score is calculated by the improved G1 method using SRC, and the DR potential is obtained. Finally, the resource schedulable capacity of a certain region is obtained. The results show that the method realizes the potential evaluation of user-side resources in a region to participate in DR, and provides data support for the power supply company to reasonably schedule user-side resources. Moreover, compared with existing methods, the proposed method greatly improves the availability of power company scheduling regional resources to participate in DR.